3D printing of okara ink: the effect of particle size on the printability - Lee, Cheng Pau (2022)
This paper discusses a method to perform direct ink writing (DIW) 3D printing of okara─a soybean byproduct generated from the production of soy milk and bean curd─without using rheology modifiers. Food additives are commonly added to food inks to modify the rheological properties to improve printability and ensure the fidelity of the printed structures. The use of additives may, however, cause unintended changes in the texture and flavor of the original foods. To overcome this challenge, we identified the particle size and concentration of okara that achieve desired rheological properties to ensure 3D printability. Our measurement suggested the particle sizes were an essential variable to determine the rheological properties of the okara ink. 3D printable okara inks were demonstrated with 33% w/w of okara powders with particle sizes of <100 μm, which gave the yield stress of 200 ± 40 Pa and the storage modulus of 23300 ± 300 Pa. Using the formulated okara ink, we fabricated 3D structures to achieve different textures, which was identified by texture profile analysis (TPA). This study suggests a simple route to formulate water-insoluble powder-based foods into printable ink without additional rheology modifiers. This work also highlights a unique route to upcycle the food waste (i.e., okara powders) into visually appealing snacks with customized texture, highlighting the potential use of 3D food printing to improve food sustainability.